Revision of Heringina Aczél, 1940 (Diptera: Tephritidae), with description of a new species from Iran and Turkey - Namin, Saeed Mohamadzade; Korneyev, Severyn V. (Zootaxa, 2015)
The genus Heringina Aczél, 1940 is revised and shown to belong to the Tephritis group of genera and is closely related to Tephritis and Multireticula. Literature records are revised, and available collection material is listed. The genus includes two species: H. guttata (Fallén 1814) originally described from the sand dunes of southern Sweden and occurring from the Baltic region through Ukraine and Caucasus to Turkey, Iran, Kazakhstan, and Kyrgyzstan, and Heringina arezoana sp. nov., found in Iran and eastern Turkey. Both species are described, illustrated, and keyed. Host plants and localization of larvae remain unknown; adult flies of both species are commonly swept from (but never reared) flower heads of Helichrysum arenarium. Other records of host plants listed by Boie (1847) and repeated in most important European monographs, are obviously based on misidentified flies. Possible relationships of Heringina with Tephritis and Multireticula are discussed.